(untitled) (Bangladesh Journal of Medical Science, 2025)
Skin is the largest organ of the human body which is affected by aging. The objective of this review paper is to briefly highlights the factors responsible for skin changes in aging and the role of nutraceutical synergies in counteracting the signs of aging. Ageing is a multifaceted biological process impacting skin health through intrinsic genetic programming and extrinsic environmental factors. Intrinsic ageing, characterized by hormonal changes and fibroblast dysfunction, and extrinsic factors, such as reactive oxygen species and advanced glycation end-products, compromise skin structure and function. Modern lifestyles, including poor nutrition, environmental pollutants, and UV exposure exacerbate oxidative stress and accelerate skin ageing. Nutraceutical interventions demonstrate significant potential in mitigating these effects, including collagen peptides, hyaluronic acid, nicotinamide mononucleotide, and trace elements like zinc and copper. These bioactive compounds promote collagen synthesis, enhance hydration, and reduce oxidative stress, improving skin elasticity, hydration, and resilience. This study emphasizes the efficacy of a multi-nutraceutical approach, which synergistically addresses ageing pathways, providing a promising avenue for personalized, effective anti-ageing strategies. Future research is recommended to focus on long-term, populationdiverse studies to validate these findings and expand their applicability. BJMS, Vol. 24 No. 04 October’25 Page : 1072-1078